Age-related decline in positive emotional reactivity and emotion regulation in a population-derived cohort. Issue 6 (23rd May 2019) - Schweizer, Susanne; Stretton, Jason; Van Belle, Janna; Price, Darren; Calder, Andrew J; ,; Dalgleish, Tim
Abstract: Human older age ushers in functional decline across the majority of cognitive domains. A notable exception seems to be affective processing, with older people reporting higher levels of emotional well-being. Here we evaluated age-related changes in emotional reactivity and regulation in a representative subsample ( N  = 104; age range: 23–88 years) of the population-derived Cambridge Centre for Ageing and Neuroscience cohort. Performance on a film-based emotion reactivity and regulation task in the magnetic resonance imaging scanner showed an age-related decline in positive reactivity, alongside a similar decline in the capacity to down-regulate negative affect. Decreased positivity with age was associated with reduced activation in the middle frontal gyrus. These findings, from the largest neuroimaging investigation to-date, provide no support for age-related increases in positive emotional reactivity.